Green synthesis of multifunctional MgO@AgO/Ag2O nanocomposite for photocatalytic degradation of methylene blue and toluidine blue - Zidane, Younes; Laouini, Salah E.; Bouafia, Abderrhmane; Meneceur, Souhaila; Tedjani, Mohammed L.; Alshareef, Sohad A.; Almukhlifi, Hanadi A.; Al-Essa, Khansaa; Al-Essa, Ethar M.; Rahman, Mohammed M.; Madkhali, Osama; Menaa, Farid (Frontiers in Chemistry, 2022)
Introduction: In this paper, MgO@AgO/Ag2O nanoparticles were greenly synthesized, the current idea is to replace the harmful chemical technique with an ecofriendly synthesis of metal oxide nanoparticles (NPs) utilizing biogenic sources. Methods: The current investigation was conducted to create silver oxide NPs decorated by MgO NPs (namely, MgO@AgO/Ag2O nanocom-posite) using the leaves extract of Purslane (Portulaca Oleracea) as the reducing and capping agent. The nanopowder was investigated by means of X-ray diffraction, scanning electron mi-croscope, BET surface area, Fourier transform infrared, and UV-vis spectrophotom-eter studies. XRD studies reveal the monophasic nature of these highly crystalline silver nano-particles. SEM studies the shape and morphology of the synthesis AgO/Ag2O and MgO@AgO/Ag2O NPs. The presence of magnesium and oxygen was further confirmed by EDS profile. Results and discussion: The surface area was found to be 9.1787 m2/g and 7.7166 m2/g, respectively. FTIR analysis showed the presence of specific functional groups. UV-vis spectrophotometer studies show the absorption band at 450 nm due to surface plasmon resonance. The results have also indicated the high performance of the greenly synthesized AgO/Ag2O NPs and MgO@AgO/Ag2O NPs for photocatalytic activity dye degradation (methylene blue and toluidine blue).